A combined tannic acid-copper-iron coating of ultrafiltration membrane for enhanced anti-bacterial and algal-inhibition performance. (December 2022) - Liu, Junxia; Yu, Xuri; Yang, Ennuo; Li, Tian; Yu, Hongjian; Wang, Zhihong; Dong, Bingzhi; Fane, A.G.
Abstract: Biofouling is a bottleneck in restricting ultrafiltration (UF) application for drinking water treatment. In the present study, we developed a simple, rapid, and cost-effective modification approach for both anti-bacterial and algal-inhibition enhancement of the commercially available polyvinylidene fluoride (PVDF) UF membrane. The membrane surface was successively coated with tannic acid (TA), copper ion (Cu 2+ ), and ferric ion (Fe 3+ ). The introduction of TA was to reduce Cu 2+ in situ to form copper nanoparticles (Cu 0 NPs) on the membrane for enhanced anti-bacterial ability, and to intensify the algal-inhibition efficiency of the membrane, as well as to increase the hydrophilicity of the coating layer. In addition, the ferric ion formed a coordinated complex compound with TA to enhance the stability of the coating layer. The resultant membrane showed an excellent ability for simultaneous anti-bacterial and algal inhibition performance, with a 98.9% inactivation efficiency of Escherichia coli, a 96.9% inhibition efficacy of Bacillus subtilis, and a 100% extermination of Microcystis aeruginosa without sacrificing the water flux at a molar ratio of 1:1:0.1 for TA-Cu-Fe. The facile TA-Cu-Fe coating process with the intensified anti-biofouling ability created in this study provides a promising membrane surface modification approach for practical applications, which can be explored for further development. Graphical abstract: Unlabelled Image Highlights: A simple, rapid, effective but economic coating approach for UF was proposed. Cu 2+ was reduced by TA in situ to form Cu 0 NPs on UF membrane surface. The coated membrane exhibited excellent anti-bacterial and algal-inhibition performance simultaneously. TA enhanced the hydrophilicity of the modified membrane. The introduction of Fe 3+ intensified the stability of the coating layer.